Warrior king : the triumph and betrayal of an American commander in Iraq - Sassaman, Nathan; Layden, Joseph, 1959- (New York : St. Martin's Press, 2008)
Shares the story of the disgraced military officer who was charged for covering up the alleged drowning of an Iraqi by his men, describing his West Point background and successful battlefield contributions against terrorism.
Keywords: Sassaman, Nathan; United States. -- Army -- History -- 21st century; Iraq War, 2003-2011 -- Personal narratives, American; Soldiers -- United States -- Biography; Iraq War, 2003-2011 -- Regimental histories -- United States